The Pacifying Effects of Local Religious Institutions: An Analysis of Communal Violence in Indonesia. (June 2015) - De Juan, Alexander; Pierskalla, Jan H.; Vüllers, Johannes
This paper tests whether local religious institutions have a dampening effect on the probability of communal violence. It argues that a dense layer of institutions strengthens horizontal and vertical contacts and networks within religious communities. Horizontal linkages help to bridge social, economic, and ethnic divisions. Vertical contacts enable religious leaders to stay informed about communal grievances among their followers and to coordinate conflict resolution attempts. In our analysis of more than 60, 000 villages in Indonesia, we are able to document a statistically significant and substantively meaningful negative effect of the density of local religious institutions on the probability of mass fighting. This effect is robust to the inclusion of an exhaustive list of confounding variables and alternative measures of violence. We present additional evidence that this pacifying effect of religious institutions is weaker or absent in conflicts that evolve along explicitly religious cleavages.